Careenage, Barbados. - J. Combier, J. (The Main Library, University of the West Indies, Cave Hill Campus, Barbados is responsible for making this digital resource available., 2024)
This image shows an aerial view of the careenage in Bridgetown, Barbados. There are a signficant number of boats docked in the water. This is a divided back postcard. Back of the Postcard MP £8 (Handwritten in Pencil)
Landscape, Sephia Tone, “3 ½” x 5½ ”
Keywords: Ships; Boats; Loading docks; Piers & Wharves; Careenage